Characteristics of Islamic Corporate Social Responsibility (ICSR) Disclosures - Dedik Nur Triyanto; Lutfi Kurniatir Rohmah (The Indonesian Accounting Review, 2022)
The company’s CSR activities illustrate that, in addition to carrying out its operational activities, the company is also responsible for the sur-rounding environment. This sharia-based social performance reporting is assessed based on the sharia index developed by AAOFI (Accounting and Auditing Organization for Islamic Financial Institutions). The purpose of this study was to determine the effect of public share ownership, firm size, leverage, profitability, and corporate governance on the disclosure of Islamic Corporate Social Responsibility (ICSR). The sample was taken from 12 sharia companies registered in the Jakarta Islamic Index (JII) for the 2015-2020 period using a purposive sampling technique. The data were analysed using panel data regression analysis through the EViews 11 application. Firms and profitability affect Islamic Corporate Social Responsibility (ICSR) disclosures, and public share ownership has a negative effect on ICSR disclosures, while leverage and corporate governance variables do not affect Islamic Corporate Social Responsibility (ICSR) disclosures. Based on the results of this study, it is expected that elements in corporate governance can carry out their duties and responsibilities in carrying out their duties so that ICSR disclosure is carried out better.